Layered Heterostructures of Ultrathin Polymeric Carbon Nitride and ZnIn2S4 Nanosheets for Photocatalytic CO2 Reduction. Issue 69 (1st October 2018) - Zhou, Min; Wang, Sibo; Yang, Pengju; Luo, Zhishan; Yuan, Rusheng; Asiri, Abdullah M.; Wakeel, Muhammad; Wang, Xinchen
Abstract: The rational construction of heterostructures by using layered semiconductors with two‐dimensional (2D) nanosheet configurations is promising to improve the efficiency of CO2 photoreduction. Herein, the fabrication of layered heterojunction photocatalysts (PCN/ZnIn2 S4 ) by in situ growth of 2D ZnIn2 S4 nanosheets on the surfaces of ultrathin polymeric carbon nitride (PCN) layers is presented for greatly enhanced CO2 conversion with visible light. The solution‐processed self‐assembly strategy renders the building of uniform and intimate junctions between PCN layers and ZnIn2 S4 subunits, which remarkably accelerates the separation and transfer of photogenerated charge carriers. In addition, the layered composites can also promote CO2 adsorption and strengthen the visible‐light absorption. Consequently, the optimized PCN/ZnIn2 S4 sheet‐shaped composite shows reinforced photoactivity for deoxygenative CO2 conversion, affording a high CO‐production rate of 44.6 μmol h −1, which is 223 times higher than that of the pristine PCN nanosheets. Moreover, the heterojunction photocatalyst also exhibits high stability during repeated runs for five cycles. Abstract : Layered heterostructures of PCN/ZnIn2 S4 are constructed by the solution‐processed self‐assembly strategy. The layered composites show reinforced photoactivity for deoxygenative CO2 conversion, ascribed to the accelerated separation of charge carriers, enhanced CO2 adsorption, and increased visible‐light absorption.